Ornamento aventura errante - Albuquerque, Aline Mourão de (2016)
An adornment can be understood as the trace of a gesture, in which it is possible to sense the presence of both the manual work and the thought process, bringing it closerto the concept of artifact, in which the aesthetic and functional qualities are inseparable. Taking this idea as a starting point, it is possible to free it from the stigma of accumulation, excess and frivolity placed upon it by the “official” history of Western art in the name of progress, therefore imparting political potency to the subjectivity of its non-representative aesthetics. This project proposes a multifocal approach to the adornment as a type of device capable of giving agency to an intimate dimension of the creative gesture and to the countless possibilities of making it visible, especially through photography and on urban spaces, subtly intervening with the surfaces of the cities and with people's lives.